Endogenous monetary approach to optimal inflation–growth nexus in Swaziland. Issue 4 (18th March 2020) - Phiri, Andrew
Abstract : Purpose: The purpose of our study is to examine the inflation–growth nexus relationship for Swaziland between 1975 and 2016 with the intention of estimating an optimal level of inflation, which maxims economic growth or minimizes growth losses. Design/methodology/approach: We estimate on an endogenous monetary model of economic growth augmented with a credit technology using a smooth transition regression (STR) model, which allows us to estimate an optimal inflation rate characterized by smooth transition between different inflation regimes. Findings: Our empirical results point to an inflation threshold estimate of 7.64 per cent at which economic growth gains are maximized or similarly growth losses are minimized. In particular, we find that above this threshold economic agents may be able to protect themselves from inflation through credit technology and a more urbanized population and yet such high inflation adversely affects the influence of exports on economic growth. This noteworthy since a majority of government revenues is from trade activity via the country's affiliation with the Southern African Customs Union (SACU). Originality/value: The major contribution of this paper is that it becomes the first to draw directly from endogenous growth theory to estimate the inflation threshold for any African country, which will hopefully pave a way for similar studies on other African countries.